IMPLEMENTASI KEBIJAKAN SERTIFIKASI GURU DALAM MENINGKATKAN KINERJA GURU DI SMA NEGERI 2 TONDANO - Masengi, Evi Elvira; Lumingkewas, Elvis; Supit, Brain Fransisco (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aimed to analyze 1) the certified teachers performace in the learning process, 2) factors that hinder the certified teachers low performance, 3) the principal’s efforts to overcome obstacles to the certified teachers performance. The method used is a qualitative research method at SMA Negeri 2 Tondano. The study results are 1) The certified teachers performance is still low in discipline, skill of teaching and making learning tools; 2) Inhibiting factors are low ability (knowledge) and skills, lack of motivation from superiors, lack of control or supervision by school principals, lack of courage of school principals in taking firm action, lack of training in making learning tools and not mastering information technology; 3) Efforts made by school principals to improve the performance of certified teachers are firm in reprimanding and imposing sanctions, conducting training in making learning tools and having to master information technology and carry out continuous evaluations.